Her holiday hero - Daley, Margaret; Copyright Paperback Collection (Library of Congress) (New York : Harlequin Love Inspired, 2013)
The holidays are right around the corner, but Captain Jake Tanner is struggling to find Christmas cheer. Having survived a devastating attack overseas, he has emotional scars that run deep. When Jake meets beautiful widow Emma Langford, his heart is unprepared for the feelings she inspires. Training service dogs has taught Emma to recognize those in need. She wants to show Jake that a four-legges companion is the best therapy, but she's afraid that the closer she gets, the more her own wounds are revealed. Together, Jake and Emma will discover it takes a different kind of bravery to opem themselves to love - and to healing.
"Love inspired inspirational romance."
Includes discussion questions
Keywords: Veterans -- Mental health -- United States -- Fiction; Widows -- Fiction; Service dogs -- Fiction; Love stories; Christmas stories; Religious fiction